Postmodern Brodomerkur office building in Split by the architect Danko Colnago, 1985-1990 - Ožić Bašić, Dina (Array, 2021)
This paper contributes to the knowledge of the postmodern architecture of the 1980s in the City of Split. It focuses on the Brodomerkur Office Building, which is an outstanding example of postmodern office space in the urban heart of Split. The study analyses the building's urban and architectural features, which are evaluated in both a local and global context. The Brodomerkur Office Building's unique design makes it an architectural gem worthy of landmark status and preservation.